Education of Household Members and Nutritional Status of Children in Bangladesh - Akhter, Halima; Haque, M Ershadul (Dhaka University Journal of Science, 2018)
Malnutrition is the burning question all over the world’s public health. Bangladesh is one of those countries where level of malnutrition of infant and child is very serious and many problems that results from malnutrition in Bangladesh. The aim of this study is to substantiate whether there exists any influence of parents’ education for child nutrition as well as to find out the potential effects of non-parental household member’s literacy level on child malnutrition. In this study we have found that parents’ education is an important factor for child nutrition. Also other household members’ education has significant impact on stunting (height for age) and underweight (weight for age). The results of this study focus the policies that encourage participation in schools and higher education program as well as improve economic condition of the households to dilute child malnutrition in Bangladesh. Dhaka Univ. J. Sci. 66(1): 1-7, 2018 (January)